SARS-CoV-2 and Angiotensin-Converting Enzyme-2 Receptor Interaction Blocker– an In-Silico Approach: In-Silico Analysis of SARS-CoV-2 and ACE-2 Receptor Interaction Blockers - Khan, Zoha; Suleman, Muhammad; Tariq, Hamna; Mumtaz, Mehvish; Azam, Hafiz Muhammad Husnain; Hussain, Nazim; Sarfraz, Hadia; Baqar, Zulqarnain; Munir, Haris; Zulfiqar, Moeen (Pakistan Journal of Health Sciences, 2024)
The global COVID-19 pandemic, instigated by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has led to substantial morbidity and mortality on a worldwide scale. While COVID-19 vaccines offer hope, the emergence of mutated viral strains necessitates the development of FDA-approved drugs to address future outbreaks. Objective: To examine prospective antiviral medications through an analysis of the interaction between the spike protein of SARS-CoV-2 and Angiotensin-converting enzyme-2 (ACE-2) receptors, which play a pivotal role in facilitating viral entry into host cells. Methods: Molecular docking was employed to assess the binding affinities of various protease inhibitors with ACE-2 receptors. Natural proteases, including Furin and Transmembrane serine protease 2 (TMPRSS2), cleave viral spike proteins into S1 and S2 subunits, facilitating fusion with ACE-2 receptors. We assessed the binding energies of Indinavir, Nafamostat, Fosamprenavir, Lopinavir, and Boceprevir to inhibit this interaction with a sense of optimism for their potential therapeutic applications. Results: Our findings suggest potential treatments for COVID-19, with Indinavir, Nafamostat, Fosamprenavir, Lopinavir, and Boceprevir displaying promising binding energies of -9.6 kcal/mol, -8.4 kcal/mol, -7.7 kcal/mol, and -7.5 kcal/mol, respectively. Conclusions: While promising, further clinical trials are important to potentially evaluate the efficacy and safety of these proposed drugs in combating COVID-19 and its variants.